Testing Of The Validity of Interactive Learning Module on Creative and Entrepreneurs Learning Products - Rini Sefriani; Indra Wijaya; Menrisal Menrisal; Muharika Dewi (Journal of Educational Science and Technology (EST), 2020)
This study aims to determine the level of validity of Interactive Learning Modules in Creative Product and Entrepreneurship Subjects in Vocational Schools. The method used in this research is the 4-D Research and Development method. The steps of this research and development method are: (1) define, (2) design, (3) develop, and (4) assess. Based on research that has been done, the average value of the validator test assessment of the Creative Learning and Entrepreneurship Interactive learning module is 91.92%, so that the level of validity can be interpreted very validly used. In conclusion, based on the assessment and input from experts that the Interactive Learning Module on the subject of Creative Products and entrepreneurship in High Schools and Vocational Schools is feasible to be used in learning Creative Products and Entrepreneurship in Vocational High Schools.